1992
DOI: 10.1016/0020-7292(92)90974-n
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage- and lymphocyte-subtypes in the endometrium during different phases of the ovarian cycle

Abstract: The presence of immunocompetetive cells in the endometrium during the proliferative and secretory phase of the ovarian cycle is demonstrated on the light and electron microscopic level using monoclonal antibodies (MoAb). Subtypes of monocytes, macrophages and T-lymphocytes appear during the different phases in variable extent and different localization. Some subpopulations of the monocyte/macrophage system and T-helper lymphocytes increase in number on day 21/22. Our observations indicate that cells with bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 12 publications
6
45
0
2
Order By: Relevance
“…Macrophages constitute 10% of CD45 cells (general leukocyte antigen) in a non-pregnant endometrium and 20-30% of the cells in the deciduas in the first trimester [2,10]. In a study on subclasses of leukocytes in the endometrium at the time of implantation and early gestation [23], the rate of CD68 positive macrophages was found to increase, which is comparable with the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Macrophages constitute 10% of CD45 cells (general leukocyte antigen) in a non-pregnant endometrium and 20-30% of the cells in the deciduas in the first trimester [2,10]. In a study on subclasses of leukocytes in the endometrium at the time of implantation and early gestation [23], the rate of CD68 positive macrophages was found to increase, which is comparable with the present study.…”
Section: Discussionsupporting
confidence: 78%
“…The uterine mucosa normally contains macrophages [2,3], dendritic cells and natural killer (NK) cells [4,5] in addition to T lymphocytes [3,6] and B lymphocytes [7]. Following implantation, the cellular architecture of the uterine mucosa is reorganized.…”
Section: Introductionmentioning
confidence: 99%
“…The similar findings were pointed out by several publications. 36,37 Tie-2 expressing BM-derived EPCs need vasculogenic environments introduced by angiogenic cytokines secreted from BM-derived macrophages. Therefore, this balance of EPCs and macrophages might play a pivotal role in neovascularization in endometrial formation.…”
Section: Masuda Et Al Estrogen and Endothelial Progenitor Cellsmentioning
confidence: 99%
“…Others have reported low levels of MHC class II on the columnar epithelial cells of the endocervix (Hussain et al, 1992), and in vitro studies demonstrated that isolated cells from the cervix (3/5 tissues) as well as the vagina (3/3) were functionally capable of presenting antigen (Fahey et al, 1999). Distributed primarily between the epithelial and myometrial layers, macrophages are found both scattered throughout the Fallopian tubes, cervix, and vagina and in small aggregates in the uterus (Bonatz et al, 1992;Kamat and Isaacson, 1987;Loke and King, 1995;Marshall and Braye, 1987). Macrophages represent approximately 10% of the FRT leukocytes (Givan et al, 1997), with higher presence in endometrial stroma and myometrial connective tissue than in the endoor ectocervix (Kutteh et al, 2005).…”
Section: Antigen-presenting Cellsmentioning
confidence: 95%
“…The human reproductive tract contains a full spectrum of leukocytes with the potential to function in ways similar to those present at other mucosal tissues and in the peripheral blood (Dahlenbach-Hellweg, 1975;Bonatz et al, 1992;Kamat and Isaacson, 1987;Laguens et al, 1990;Morris et al, 1985;Loke and King, 1995). Although the precise function of these cells in the female reproductive tract remains to be established, a role in surveillance against aberrant trophoblast proliferation and uterine invasion has been proposed (King et al, 1996).…”
Section: Cells Of the Immune System In The Female Reproductive Tractmentioning
confidence: 97%